Vendor Industry: Revolution in Economic Growth - Ahmad, Nisar (Journal of Social and Development Sciences, 2012)
The developing countries with ample human resources can be the major benefactors of vendor industry. Such countries have high potential of using people, who otherwise may be fully or partially unemployed most of the time. Poor countries are not benefiting because of financial/material foreign assistance from rich countries. In fact, many of these countries are accumulating huge foreign debts without any trickledown effect to improve the economic welfare of the common person. Poor people because of lack of education and opportunities to earn income are forced to live with minimum of food intake and poor health facilities. Empowering the common person should be the ultimate aim where national resources are to be employed. This will necessarily mean reversing national priorities, which presently seem to have painfully neglected the welfare of the majority of people living in the poor countries. The suggested model in this Paper presents an approach similar to the one adopted by the Grameen Bank. The idea was to extend interest free small loans to the eligible families (having required skill and basic education) to do business on their own. However, all this is to be handled through the private sector, and monitored by the banking authorities for repayment of all those loans within a feasible period. This Paper provides strong justification for expanding vendor industry in developing countries on terms and conditions, which can motivate and provide incentives for the poor families to earn and live an honorable life of comfort and respect in the society. The Paper analysis the effectiveness of the western advocated theories of economic growth and suggests a complete turnaround in the philosophy of national resource use. The economic growth concept advocated in this Paper is built on the ground that the developing countries cannot benefit from the foreign assistance, rather the people (a valuable resource for the poor countries) in these countries need to be focused, educated, trained and provided with the opportunities to work and to do business in their specialized domain so that they can add value to the national product (GDP).